2019
DOI: 10.1111/apt.15258
|View full text |Cite
|
Sign up to set email alerts
|

The incidence of cancer and mortality in paediatric onset inflammatory bowel disease in Denmark and Finland during a 23‐year period: a population‐based study

Abstract: Background: Recent studies report increased risks of both cancer and mortality in paediatric onset inflammatory bowel disease (pIBD) but the reproducibility of this is unknown. Aim: To estimate the risk of cancer and mortality in the Danish and Finnish pIBD population in a 23-year period compared to the general population. Methods: The pIBD population was defined as individuals registered in the national patient registries with a diagnosis of Crohn's disease (CD), ulcerative colitis (UC) or IBD-unclassified be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
59
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(65 citation statements)
references
References 35 publications
5
59
0
1
Order By: Relevance
“…As stated in the editorial by Drs Banerjee and Gearry, the main result of the present study is the finding of an increased risk of cancer and mortality in pIBD with a surprisingly high risk of suicide. In contrast to the adult literature on this subject, the paediatric literature almost unambiguously reports an increased risk of cancer in pIBD and the main question is no longer if there's an increased risk but why.…”
supporting
confidence: 55%
See 1 more Smart Citation
“…As stated in the editorial by Drs Banerjee and Gearry, the main result of the present study is the finding of an increased risk of cancer and mortality in pIBD with a surprisingly high risk of suicide. In contrast to the adult literature on this subject, the paediatric literature almost unambiguously reports an increased risk of cancer in pIBD and the main question is no longer if there's an increased risk but why.…”
supporting
confidence: 55%
“…The authors' declarations of personal and financial interests are unchanged from those in the original article …”
Section: Acknowledgementmentioning
confidence: 99%
“…However, to our knowledge, no studies have investigated whether differences in disease course between pUC and aUC could be explained by differences in the initial disease extent. Lastly, recent reports have found an increased risk of cancer in pIBD, possibly due to a more extensive and aggressive disease state compared to aIBD …”
Section: Introductionmentioning
confidence: 92%
“…Usually when we consider causes of death in patients with IBD, cancer, venous thromboembolism, sepsis and nutrition are at the front of mind. However, the population‐based retrospective study by Malham et al has made us think more laterally about mortality in young people with IBD, and challenges us to be more vigilant for mental health issues.…”
mentioning
confidence: 99%
“…In their study, Malham et al identified all Danish and Finnish patients diagnosed with paediatric inflammatory bowel disease (pIBD) over a 23‐year period . They cross‐linked each patient to the national cancer registries and the national cause of death registries to estimate cancer and mortality risks for their pIBD cohort.…”
mentioning
confidence: 99%